The Effect of Leaders’ Coaching Behaviors on Employee Learning Orientation: A Regulatory Focus Perspective - Liu, Wei; Xiang, Shuting (Frontiers in Psychology, 2020)
Although scholars have recognized leaders’ importance in facilitating employee learning, the potential role that leaders’ specific behaviors play in followers’ learning outcomes remains elusive. Based on the literature, we identified two styles of leaders’ coaching behaviors that may promote followers’ learning, namely encourage-to-explore behaviors and guide-to-learn behaviors. We expect that these two styles of coaching behaviors would have different relationships with employee learning orientation, moderated by employees’ regulatory focus. To test our hypotheses, we conducted two studies: an experimental study using scenarios of leader behavior with data collected from 124 undergraduate students (study 1), and a field study with data from 334 pairs of employees and their direct supervisors (study 2). Results showed that encourage-to-explore behaviors had a positive relationship with employee learning orientation, whereas guide-to-learn behaviors had an inverted U-shaped relationship with employee learning orientation. When employees had low levels of promotion regulatory focus, encourage-to-explore behaviors showed a positive correlation with employee learning orientation. However, when they had low levels of prevention regulatory focus, employee learning orientation increased as the guide-to-learn behaviors increased; this increased up to an intermediate level and then decreased. As such, this study provides novel theoretical and empirical insights into leadership and learning.